UNDERSTANDING GENDER JUSTICE PERSPECTIVE AMIN WADUD MUHSIN - Ari Susetiyo; Zetty Azizatun Ni'mah (IAIN Kediri, 2022)
Understanding or interpretation of a text, including the holy book of the Qur'an, is strongly influenced by the perspective of the commentator, cultural background, and prejudices behind it. In this way the text becomes alive and rich in meaning. The meaning of the text becomes dynamic and always contextual, along with the acceleration of the development of human culture and civilization. Amina Wadud carries out her creativity and innovation in interpreting the Qur'an. Because so far there is no truly objective method of interpretation. Each interpretation tends to reflect subjective choices. The reconstruction of Amina Wadud's interpretation methodology is characterized by Deconstructive-reconstructive, Argumentative-theological and Hermeneutic-philosophical, each verse to be interpreted must be analyzed in various aspects. n the study of leadership, Amina's critique of the male Mufassir that men were created by Allah to be superior to women (in terms of physical and mental strength) ignores the sociological contextual aspect which is contrary to the spirit of justice and humanity in Islamic teachings.